Inequality and Growth: The Dual Role of Human Capital in Development - Theo Eicher (Center for Economic Studies and ifo Institute (CESifo), 2000)
To examine how human capital accumulation influences both economic growth and income inequality, we carefully endogenize the demand and supply of skills. We explicitly introduce the costs and externalities in education, and examine how both relate to learning-by-doing and R&D intensity. In addition, we endogenize the determinants of the skill-bias of labor demand: the complementarity between technology and skilled and unskilled labor. Our results identify parameters that are central to the evolution of inequality during the development process. We characterise development thresholds when countries switch endogenously from pure learning to directed R&D, and we show that technical change can generate multiple steady states that are consistent with the cross-country data on inequality and skill-premia.
Keywords: J31; O40; 330; Human capital; wage inequality; biased technical change; threshold externalities